Status Gizi Ibu Hamil Di Kecamatan Pattalassang, Gowa (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
The purpose of the study was to see the relationship between household characteristics and the nutritional status of pregnant women in Pattallassang District, Gowa Regency. Methods: This study used an analytical survey method. The study population consisted of all pregnant women found in the working area of the Pattalassang Community Health Center. The cluster sampling technique was applied to determine the part of the district/city. Data collection was carried out by trained personnel including 1x24 hour withdrawal, weight, height, and upper arm circumference (UAC). The data were analyzed using the SPSS 20 program. The determination of the risk of CED was based on LiLA <23.5 cm. Results: In general, pregnant women in this study were on average 26-35 years old (52%). Among them 36% only graduated from elementary school, the average gestational age of a mother is in the second trimester, and all of them are Muslim. The prevalence of CED risk is 18%. The relationship between education and nutritional status of pregnant women with a significance value of p = 0.089 (p> 0.05). The relationship between family income and nutritional status of pregnant women has a significance value of p = 0.664 (p> 0.05). Conclusion: there is no significant relationship between income and education with nutritional status.